Corruption and Environmental Degradation: Evidence from the EECCA Region - Yildirim, Abdulmecit; İşlek, Hüseyin; Okumuş, İlyas (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This research introduces a novel analytical approach to examine the interactions among corruption, per capita income, and the environment across the member countries of the GREEN Action Task Force platform. The study finds that lower-income countries experience a larger reduction in environmental degradation when corruption declines. Research Objective: The study aims to determine the effect of corruption on CO2 emissions and to examine how this relationship changes with economic development. Moreover, the research tests the validity of the Environmental Kuznets Curve hypothesis within this specific context. Research Method: The study used the Driscoll-Kraay and FGLS methods to address potential cross-section dependence, heteroskedasticity, and autocorrelation issues that commonly arise in panel data analysis. Empirical Results: Corruption has a significant negative effect on CO2 emissions. The interaction between corruption and per capita income reveals that the impact of reduced corruption on CO2 emissions is more apparent in countries with lower per capita income. The study also confirms the validity of the Environmental Kuznets Curve hypothesis. Implications: Policymakers, particularly in lower-income countries, should prioritize anti-corruption policies to protect the environment during economic development. JEL Classification: D73, Q42, Q53, Q56